2020
DOI: 10.4174/astr.2020.99.5.275
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of postoperative quality of life following minimally invasive gastrectomy for gastric cancer: a prospective cohort from Korean multicenter robotic gastrectomy trial

Abstract: Purpose Quality of life (QOL) has become important in the trend of emphasizing patient satisfaction. This study aimed to evaluate the QOL in patients who underwent laparoscopic or robotic gastrectomy for gastric cancer. Methods A prospective trial was performed involving patients who underwent laparoscopic or robotic gastrectomy for primary gastric cancer at 11 hospitals in Korea. Within this comparative trial, QOL, postoperative pain, and long-term complications were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…In this study, we found that the incidence of dysphagia symptom was higher in patients with total and proximal gastrectomy. This is consistent with studies from Lee et al (22) and Choi et al (23) suggesting that the dysphagia symptom was worse in the total gastrectomy group. Because of the disharmony and inconsistency of contraction and peristalsis between the esophagus and jejunum, patients with total or proximal gastrectomy sometimes suffer from dysphagia when eating.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we found that the incidence of dysphagia symptom was higher in patients with total and proximal gastrectomy. This is consistent with studies from Lee et al (22) and Choi et al (23) suggesting that the dysphagia symptom was worse in the total gastrectomy group. Because of the disharmony and inconsistency of contraction and peristalsis between the esophagus and jejunum, patients with total or proximal gastrectomy sometimes suffer from dysphagia when eating.…”
Section: Discussionsupporting
confidence: 93%
“…( 22 ) and Choi et al. ( 23 ) suggesting that the dysphagia symptom was worse in the total gastrectomy group. Because of the disharmony and inconsistency of contraction and peristalsis between the esophagus and jejunum, patients with total or proximal gastrectomy sometimes suffer from dysphagia when eating.…”
Section: Discussionmentioning
confidence: 91%
“…Objective measurements including blood test, imaging exam, and body composition analysis are widely used for assessing these changes. Although the QOL questionnaire is a subjective indicator, it has become increasingly important as a soft measurement in assessing both surgical and oncological outcomes [ 18 ]. Body weight loss is another objective indicator that varies widely among patients after surgery and is reported to have a marked impact on postoperative QOL changes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%